Medication adherence, related factors and outcomes among patients with pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension: a systematic review - Antoine Le Bozec; Virginie Korb-Savoldelli; Claire Boiteau; Agnès Dechartres; Salma Al Kahf; Olivier Sitbon; David Montani; Xavier Jaïs; Christophe Guignabert; Marc Humbert; Laurent Savale; Marie-Camille Chaumais (European Respiratory Review, 2024)
Introduction Pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) are life-threatening conditions that can progress to death without treatment. Although strong medication adherence (MA) is known to enhance outcomes in chronic illnesses, its association with PAH and CTEPH was sporadically explored. This study aims to examine the MA of patients with PAH or CTEPH, identify factors associated with low adherence and explore the resulting outcomes. Methods A systematic review was conducted by searching multiple databases (Medline, Embase, Cochrane Central, ClinicalTrials.gov, Scopus, Web of Science and Google Scholar) from 6 March 1998 to 6 July 2023. We included studies reporting MA as primary or secondary end-points. Study selection, data extraction and methodological quality assessment were performed in duplicate. Results 20 studies involving 22 675 patients met the inclusion criteria. Heterogeneity was observed, particularly in the methods employed. MA means ranged from 0.62 to 0.96, with the proportion of patients exhibiting high MA varying from 40% (95% CI 35–45%) to 94% (95% CI 88–97%). Factors associated with low adherence included increased treatment frequency, time since diagnosis and co-payment. High MA seems to be associated with reduced hospitalisation rates, inpatient stays, outpatient visits and healthcare costs. Conclusions This systematic review underscores the heterogeneity of MA across studies. Nevertheless, the findings suggest that high MA could improve patients’ clinical outcomes and alleviate the economic burden. Identifying factors consistently associated with poor MA could strengthen educational efforts for these patients, ultimately contributing to improved outcomes.